Application of CCME Water Quality Index to Assess the Suitability of Water for Protection of Aquatic Life in Al- Radwaniyah-2 Drainage in Baghdad Region - Rabee, Adel Mashaan; Hassoon, Hasanain Abbood; Mohammed, Ahmed Jasim (Al-Nahrain Journal of Science, 2018)
The Canadian Council of Ministries of the Environment (CCME) Water quality index used in this study for rating water quality in Al- Radwaniyah-2 drainage indicates that the quality of water in all studied stations is poor. The studied water parameters in it usually deviate from normal levels and the water is not capable to protect or support ample aquatic life. The Results showed that the TDS, Total hardness, Turbidity, Magnesium, Total coliform and Fecal coliform are the main factors responsible for deterioration of the drainage water quality. These parameters need to different procedures to maintain the quality of water in order to protect aquatic life or for any other uses.